Evaluation of the Preventive and Interceptive Orthodontic Treatment Need of an Inner City Group of Anatolian Turkish Children - Cenk Doruk; Zeynep Çoban Büyükbayraktar (Cumhuriyet University, 2019)
Objectives: The aim of this study is to examine the oral and dental health among the primary school children in a city in Turkey and to identify the need for preventive and interceptive practices.Materials and Methods: Our study was carried out on total 334 individuals, which include 135 male and 199 female primary school students between 6 and 9 years of age in Sivas, Turkey. These individuals were examined intraorally in the school environment. In order to determine the need for preventive and interceptive orthodontic treatment, pre-prepared data forms were filled in during the examination and existing problems were recorded. Collected data were evaluated through the program of SPSS (Ver:15.0). Results: The number of the individuals, who needed at least one of the preventive and interceptive orthodontic treatments was 319 (95.5%). The most required one among these practices was found as fissure sealant with a ratio of 52.1%. When the relationship between age and gender data and other parameters was evaluated, a significant relation was observed only between age and the fissure sealant, space maintainer need and posterior cross bite.Conclusions: The need for preventive and interceptive treatments was quite high and it is a fact that a special attention should be paid to these applications.